Long‐time coherent integration for high dynamic DSSS signal. Issue 21 (7th October 2019) - Wang, Fengyu; Yang, Jun; Tian, Jing; Cui, Wei; Xiang, Jinzhi
Abstract : A novel coherent integration method for high dynamics direct sequences spread spectrum (DSSS) signal is presented. The presented method is based on adjacent cross‐correlation function (ACCF) and Lv's distribution (LVD). ACCF is firstly used to compensate the code phase drift and reduce the Doppler frequency migration order. After that, LVD is used to accomplish the integration and obtain the parameter estimates. The presented method can estimate motion parameters without any searching procedure. Compared with the existing methods, the presented method can achieve a good balance between the computational cost and the detection and estimation performance. Numerical simulations are provided to verify the effectiveness of the proposed method.